GSK-3β, a pivotal kinase in Alzheimer disease - Llorens-Marítin, María; Jurado, Jerónimo; Hernández, Félix; Ávila, Jesús (Frontiers in Molecular Neuroscience, 2014)
Alzheimer disease (AD) is the most common form of age-related dementia. The etiology of AD is considered to be multifactorial as only a negligible percentage of cases have a familial or genetic origin. Glycogen synthase kinase-3 (GSK-3) is regarded as a critical molecular link between the two histopathological hallmarks of the disease, namely senile plaques and neurofibrillary tangles. In this review, we summarize current data regarding the involvement of this kinase in several aspects of AD development and progression, as well as key observations highlighting GSK-3 as one of the most relevant targets for AD treatment.